A novel MBD5 mutation in an intellectually disabled adult female patient with epilepsy: Suggestive of early onset dementia?. Issue 8 (9th July 2019) - Verhoeven, Willem; Egger, Jos; Kipp, Janneke; Verheul‐ aan de Wiel, Jiska; Ockeloen, Charlotte; Kleefstra, Tjitske; Pfundt, Rolph
Abstract: Background: The minimal critical region in 2q23.1 deletion syndrome comprises one gene only, that is, the methyl‐CpG‐binding domain protein 5 ( MBD5 ) gene. Since the phenotypes of patients with deletions, duplications or pathogenic variants of MBD5 show considerable overlap, the term MBD5 ‐associated neurodevelopmental disorder (MAND) was proposed. These syndromes are characterized by intellectual disability, seizures of any kind and symptoms from the autism spectrum. In a very limited number of patients, MAND may be associated with regression starting either at early infancy or at midlife. Methods: The present paper describes a severely intellectually disabled autistic female with therapy resistant complex partial epilepsy starting at her 16the with gradual cognitive and behavioral regression towards her sixth decade. Results: Cognitive and behavioral regression occurred towards the patient's sixth decade. Exome sequencing disclosed a novel heterozygous pathogenic frameshift mutation of MBD5 that was considered to be causative for the combination of intellectual disability, treatment‐resistant epilepsy and autism. Conclusion: The presented patient is the second with a pathogenic MBD5 mutation in whom the course of disease is suggestive of early onset dementia starting in her fifth decade. These findings stress the importance of exome sequencing, also in elderly intellectually disabled patients, particularly in those with autism. Abstract : The present paper stresses the importance of exome sequencing, also in elderly intellectually disabled patients, particularly in those with epilepsy and autism. Here, the course of disease of MBD5 ‐associated neurodevelopmental disorder, caused by a novel pathogenic MBD5 mutation, is suggestive of early onset dementia.